2020
DOI: 10.1007/s10578-020-01084-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Mode of Birth and Neuropsychological Development in Children Aged 4 Years: Results from a Birth Cohort Study

Abstract: The aim of this prospective longitudinal study was to examine the association between Cesarean section (CS) and child development and behavior. The sample consisted of 256 children who were born at term without serious perinatal pathologies. Their development and behavior was assessed at the age of four using Ages and Stages Questionnaire (ASQ-3), Children’s Behavior Questionnaire and Strength and Difficulties Questionnaire. Multivariate linear regression analyses were conducted to assess the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
2
7
1
Order By: Relevance
“…Comparable with our findings, no significant association was observed between caesarean section and internalizing (emotional and peer problems) and externalizing (conduct and hyperactivity) domains of the SDQ in a Czech Republic cohort in children of preschool age [31]. However, the authors did not distinguish between planned and emergency caesarean section due to a small sample size (N = 256) [31].…”
Section: Comparison With Other Studiescontrasting
confidence: 68%
“…Comparable with our findings, no significant association was observed between caesarean section and internalizing (emotional and peer problems) and externalizing (conduct and hyperactivity) domains of the SDQ in a Czech Republic cohort in children of preschool age [31]. However, the authors did not distinguish between planned and emergency caesarean section due to a small sample size (N = 256) [31].…”
Section: Comparison With Other Studiescontrasting
confidence: 68%
“…Therefore, in our study, even using a classification that has been previously used in the literature, there was no differentiation made as to whether the vaginal delivery involved the use of instruments or not (for example, the use of forceps, vacuum, and spatulas), or whether the C-section was programmed or due to an emergency. Some authors have indicated that these aspects, not considered in our work, may have distinct effects on children's motor development (Tribe et al, 2018;Takács et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, we believe that the detailed and extensive assessment process of preschool motor skills conducted via systematic observation is another strong point of this work. This suggests that the assessment of motor skills was: (1) objective -not subjective as some teachers had admitted to being (Cueto et al, 2017)-and was not based on third party information, as it often occurs in studies (Khalaf et al, 2015;Takács et al, 2020), despite the limitations that this may imply (Blanco-Villaseñor and Escolano-Pérez, 2017); (2) carried out in the child's natural setting, such as at school, capturing the spontaneous motor execution by the children during recreational activities that are significant and of interest to them. This assessment is characterized by a high ecological validity (Blanco-Villaseñor and Escolano-Pérez, 2017), and allows us to overcome the ecological validity issues present in other studies on motor skill assessment (Tamplain et al, 2020); and (3) carried out using an instrument created based on the objective and context of the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations